Catalytic cracking catalyst as well as preparation method and application thereof

By increasing the molecular sieve content in the catalyst and using mesh phosphorus aluminum glue as a binder, the mechanical strength problem of the catalyst under high harsh conditions is solved, and the catalytic cracking effect with high reactivity and long life is achieved.

CN119303618AActive Publication Date: 2025-01-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310846867.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

The mechanical strength of existing catalysts is difficult to take into account under high and harsh conditions, resulting in the phenomenon of running agents and the molecular sieve content is insufficient to improve the catalytic cracking reaction activity.

Method used

Provide a catalyst containing 60-85% molecular sieve, 5-20% clay, 10-35% binder, prepared by beating and spray drying, combined with mesh phosphorus aluminum glue as binder, improve mechanical strength and reaction activity .

Benefits of technology

The catalytic performance and mechanical strength of the catalyst are significantly improved, the catalyst life is extended, and the high reactant conversion rate and ethylene propylene yield in naphtha catalytic cracking reaction are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004332734590000171
    Figure BDA0004332734590000171
  • Figure BDA0004332734590000181
    Figure BDA0004332734590000181
  • Figure BDA0004332734590000182
    Figure BDA0004332734590000182
Patent Text Reader

Abstract

The invention relates to the field of preparation of catalytic cracking catalysts, and discloses a catalytic cracking catalyst as well as a preparation method and application thereof. The invention relates to a catalytic cracking catalyst. The catalyst comprises a molecular sieve, a binder and clay, based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%; the straight tube wear index of the obtained catalyst is not greater than 3% / h, and the thermal wear index is not greater than 7% / (5h). The catalyst has the advantages of high mechanical strength and high molecular sieve proportion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic cracking catalyst preparation, and in particular to a catalytic cracking catalyst and a preparation method and application thereof. Background Art

[0002] At present, the main method for producing ethylene and propylene is steam thermal cracking. The most commonly used raw material is naphtha. However, steam thermal cracking of naphtha has the disadvantages of high reaction temperature, harsh process conditions, release of large amounts of CO2, and large losses. Catalytic cracking developed in recent years is a process for producing low-carbon olefins using petroleum hydrocarbons as raw materials, and there are many literature reports on catalysts related to it.

[0003] CN1048428C discloses a catalyst for converting petroleum hydrocarbons into low-carbon olefins, which is composed of 0-70% by weight of clay, 5-90% by weight of inorganic oxides and 10-35% by weight of zeolite.

[0004] CN1160436C discloses a method for preparing a hydrocarbon cracking catalyst, comprising mixing molecular sieve slurry, pseudo-boehmite, clay and inorganic acid by slurrying, adding or not adding aluminum sol to prepare catalyst slurry, and then spray drying, wherein the composition of the catalyst slurry is based on dry weight, and the molecular sieve accounts for 15-50%.

[0005] CN1119390C discloses a method for preparing a cracking catalyst, characterized in that molecular sieve and / or alumina sol are added before clay and inorganic acid, and inorganic acid is added after alumina sol. Preferably, inorganic acid is added after alumina sol and pseudo-boehmite. There is no special restriction on the order of adding other materials, and the catalyst slurry contains a viscosity reducer; wherein the viscosity reducer is ammonium phosphate, diammonium hydrogen phosphate or ammonium dihydrogen phosphate, or a mixture thereof, and the amount of viscosity reducer added is 0.1-2% of the dry weight of the catalyst.

[0006] CN1272406C discloses a petroleum hydrocarbon cracking catalyst for producing more low-carbon olefins, which has the following composition based on the weight of the catalyst: 0-70% clay, 5-90% inorganic oxide and 10-35% zeolite.

[0007] It can be found that the preparation method of the above-mentioned catalyst is basically suitable for the preparation of catalysts with a low or medium proportion of molecular sieves. In particular, the proportion of molecular sieve content in the catalyst preparation method aimed at increasing the production of light olefins is less than 50%. In order to improve the reaction activity of the catalyst in the catalytic cracking of naphtha to produce light olefins, it is necessary to further increase the proportion of molecular sieve components in the catalyst. However, with the increase of molecular sieve components, the proportion of components with high adhesion in the catalyst is bound to decrease, and the mechanical strength of the catalyst is difficult to take into account. Under highly harsh reaction conditions, more serious catalyst leakage will occur. Therefore, a new catalyst preparation method is needed to take into account both the high mechanical strength of the catalyst and the high molecular sieve proportion. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems existing in the prior art and provide a catalytic cracking catalyst and its preparation method and application. The catalyst of the present invention has the advantages of high mechanical strength and high molecular sieve ratio.

[0009] In order to achieve the above object, the present invention provides a catalytic cracking catalyst, which includes a molecular sieve, a binder and clay;

[0010] Based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%;

[0011] The straight tube wear index of the obtained catalyst is not greater than 3% / h, and the thermal wear index is not greater than 7% / (5h). The second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:

[0012] (1) slurrying the molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry;

[0013] (2) slurrying the first slurry and at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.1 Pa·s;

[0014] (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s;

[0015] (4) beating the third slurry with a water absorbent to obtain a fourth slurry having a solid content of 40-50 wt %;

[0016] (5) The fourth slurry is spray-dried and then calcined.

[0017] The third aspect of the present invention provides a use of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in a catalytic cracking reaction.

[0018] Through the above technical solution, the beneficial effects of the present invention include:

[0019] The catalyst provided by the present invention has a high molecular sieve content, so that the catalytic performance of the catalyst is significantly improved. The catalyst of the present invention is applied to catalytic cracking reactions, especially to naphtha catalytic cracking reactions, and has a higher reactant conversion rate and a higher ethylene and propylene yield.

[0020] At the same time, the catalyst provided by the present invention has high mechanical strength, which is beneficial to enhancing the fluidization performance and wear resistance of the catalyst, thereby increasing the life of the catalyst and achieving long-term operation. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The dry basis of the present invention refers to that obtained by calcining at 550° C. for 2 hours.

[0023] In one aspect, the present invention provides a catalytic cracking catalyst, the catalyst comprising a molecular sieve, a binder and clay;

[0024] Based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%;

[0025] The straight tube wear index of the obtained catalyst is no more than 3% / h, and the thermal wear index is no more than 7% / (5h).

[0026] The content of each component of the catalyst of the present invention is calculated by feeding ratio.

[0027] According to the present invention, preferably, the straight tube wear index of the obtained catalyst is 0.5-3% / h, and the thermal wear index is 2.5-7% / (5h).

[0028] The straight tube wear index and thermal wear index of the catalyst of the present invention are both at a relatively low level, indicating that the catalyst can maintain relatively good mechanical strength and low catalyst consumption even under operating conditions of high catalyst-to-oil ratio, high temperature and high water vapor content.

[0029] The method for determining the straight pipe wear index described in the present invention refers to standard NB / SH / T0964-2017.

[0030] The method for determining the thermal wear index of the present invention is specifically as follows:

[0031] (1) Sample treatment: Pour the sample into an evaporating dish, place it in a muffle furnace at 650°C and burn it for 1 hour. Take it out and cool it in air for 5 minutes. Place it in a desiccator. After 30 minutes, weigh 50 g ± 0.01 g of the sample and place it in the desiccator for later use.

[0032] (2) Prepare two filter paper cylinders to collect the fine powder eluted in the first hour and the fine powder eluted in the last four hours. Turn on the gas source of the device, adjust the pressure regulating valve, and adjust the gas source partial pressure range to 0.28MPa~0.32MPa. Install the filter paper cylinder at the fine powder collection port of the settler, set the through-hole gas velocity of the wear tube nozzle hole to 200m / s, pass the wet air flow at room temperature, humidify each filter paper cylinder for 15min, and weigh the filter paper cylinders in time after removing them, and record them as wt1 and wt2.

[0033] (3) Place 50g of sample into the wear tube, connect the wear tube to the settler, and connect the filter paper tube at the end of the glass elbow to collect the fine powder in the first hour. Set the heating furnace temperature to 700℃ and the gas flow rate to 1L / min. Pass gas into the system and wait for the heating furnace temperature to rise from room temperature to 700℃ at a flow rate of 1L / min.

[0034] (4) After the heating furnace temperature reaches 700°C, the gas velocity is set to 650m / s through the nozzle hole, and the wear test under hot conditions is started. Within the first hour, the settler needs to be fully knocked once every half an hour. After the first hour is up, stop the air intake, quickly remove the filter paper tube, weigh and record, and record it as wt3. Then connect the filter paper tube used to collect fine powder in the next four hours to the end of the settler, and continue the wear test under hot conditions. The settler is fully knocked once every hour. After four hours, quickly remove the filter paper tube, weigh and record, and record it as wt4. Then stop the gas and end the experiment.

[0035] The thermal wear index (HAT) is calculated as follows:

[0036] HAT=((wt4-wt2)+(wt3-wt1)) / 50×100%.

[0037] wt1——the mass of the empty paper tube after humidification to collect fine powder in the first hour, in grams (g);

[0038] wt3——the sum of the mass of the empty paper tube used to collect the fine powder in the first hour after humidification and the fine powder collected in the first hour, in grams (g);

[0039] wt2——the mass of the empty paper tube of fine powder collected four hours after humidification, in grams (g);

[0040] wt4——The sum of the mass of the empty paper tube for collecting fine powder four hours after humidification and the fine powder collected in the next four hours, in grams (g).

[0041] According to the present invention, preferably, the adhesive includes a first adhesive, a second adhesive and a third adhesive.

[0042] According to the present invention, preferably, the first binder is obtained by calcining at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina.

[0043] The present invention has no particular limitation on the source of the first binder, which can be obtained from commercial sources or prepared by conventional methods.

[0044] According to the present invention, preferably, the second binder is obtained by calcining aluminum sol.

[0045] According to the present invention, preferably, the third binder is obtained by calcining phosphate aluminum glue.

[0046] The present invention has no particular limitation on the calcination conditions. For example, the calcination conditions may be the calcination conditions in the following preparation method.

[0047] According to the present invention, preferably, the aluminum sol has an aluminum-chlorine ratio of no more than 1.4, preferably 1.2-1.3. This preferred embodiment can minimize the degree of damage to the molecular sieve framework while ensuring the bonding performance of the binder, which is beneficial to improving the reaction activity of the catalyst.

[0048] The chlorine-aluminum ratio of the aluminum sol described in the present invention is measured by an X-ray fluorescence spectrometry analysis method.

[0049] The present invention has no particular limitation on the source of the aluminum sol, which can be obtained from commercial sources or prepared in-house according to conventional methods.

[0050] According to the present invention, preferably, the phosphate aluminum gel has a network structure.

[0051] The structure of the phosphoaluminum gel of the present invention is measured by a transmission electron microscope.

[0052] In the prior art, phosphate aluminum gel generally has a dispersed spherical nanoparticle structure, which has the defects of poor bonding performance and unstable structure. However, the inventors of the present invention found in the research process that phosphate aluminum gel with a network structure has both excellent bonding performance and a stable skeleton structure, which is conducive to improving the mechanical strength of the catalyst.

[0053] According to the present invention, preferably, Al in the phosphate aluminum gel 2 O3 With P 2 O 5 The mass ratio of is 0.25-0.35. This preferred embodiment is advantageous for obtaining a phosphoaluminum colloid with a rich network structure.

[0054] The Al in the phosphate aluminum gel of the present invention 2 O 3 With P 2 O 5 The mass ratio was measured by X-ray fluorescence spectrometry.

[0055] According to the present invention, preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3. This preferred embodiment can ensure the structure and stability of the phosphate aluminum gel binder, while ensuring the stability of the molecular sieve structure, which is further beneficial to improving the reaction activity and mechanical strength of the catalyst.

[0056] The present invention has no particular limitation on the preparation method of the above-mentioned phosphate aluminum gel, as long as the phosphate aluminum gel with the above-mentioned composition and characteristics can be prepared. In order to further improve the catalytic performance of the catalyst, the present invention also provides a preparation method of the above-mentioned phosphate aluminum gel.

[0057] According to the present invention, preferably, the method for preparing the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel.

[0058] According to the present invention, preferably, the reaction conditions include: temperature of 75-85° C., and time of 1-2 h.

[0059] In the preparation method of the phosphate aluminum gel described in the present invention, by controlling the temperature of adding phosphoric acid, preferably further controlling the reaction conditions, the composition and characteristics of the prepared phosphate aluminum gel meet the above requirements, which is conducive to making the prepared catalyst have excellent catalytic performance.

[0060] The present invention has no particular limitation on the amount of the acid-soluble aluminum precursor and the phosphoric acid solution, so that in the obtained phosphate aluminum gel, Al 2 O 3 With P 2 O 5 The mass ratio is 0.25-0.35.

[0061] The present invention has no particular limitation on the amount of water used, as long as the pH of the phosphate aluminum gel is within the above range.

[0062] The present invention has a wide range of choices for the acid-soluble aluminum precursor, which can be a conventional choice in the art. Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide, preferably pseudo-boehmite.

[0063] In order to further improve the catalytic performance of the catalyst, preferably, based on the total mass of the catalyst, the mass content of the molecular sieve is 60-75%, the mass content of the clay is 5-20%, and the mass content of the binder is 16-35%.

[0064] Further preferably, based on the total mass of the catalyst, the mass content of the molecular sieve is 60-70%, the mass content of the clay is 5-15%, and the mass content of the binder is 18-30%.

[0065] According to the present invention, preferably, the mass ratio of the second binder to the first binder is 1-4, preferably 1.7-4. By adopting this preferred embodiment, the catalyst can be ensured to have good mechanical strength.

[0066] According to the present invention, preferably, the mass ratio of the second binder to the third binder is 0.3-1, preferably 0.3-0.8. By adopting this preferred embodiment, the hydrothermal stability and mechanical strength of the catalyst can be improved.

[0067] The present invention has a wide range of molecular sieve types, which can be conventionally selected in the art. Preferably, the molecular sieve is at least one of ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve.

[0068] The present invention has a wide range of clay types, which can be selected from conventional choices in the art. Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.

[0069] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, the method comprising:

[0070] (1) slurrying the molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry;

[0071] (2) slurrying the first slurry and at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.1 Pa·s;

[0072] (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s;

[0073] (4) beating the third slurry with a water absorbent to obtain a fourth slurry having a solid content of 40-50 wt %;

[0074] (5) The fourth slurry is spray-dried and then calcined.

[0075] In the prior art, the molecular sieve content of the spray-formed catalyst is relatively low, generally not higher than 40wt%. This is mainly because it is necessary to ensure that the catalyst has good mechanical strength and the wear index is maintained at 3.5-7% / h to meet the needs of the catalytic cracking reaction. When the molecular sieve content is too high, spray forming is more difficult, and the catalyst wear index is higher than 10% / h, resulting in poor catalyst stability and short life, and it is impossible to achieve long-term operation. The catalyst obtained by the method provided by the present invention overcomes the above-mentioned defects, can take into account both high mechanical strength and high molecular sieve content, and is applied to catalytic cracking reactions, especially in naphtha catalytic cracking reactions, with higher reactant conversion rate and higher ethylene propylene yield.

[0076] In the present invention, the viscosity of the second slurry is not greater than 0.1 Pa·s, preferably 0.05-0.1 Pa·s. This preferred embodiment is advantageous for obtaining a uniform catalyst (ie, each component is evenly distributed).

[0077] In the present invention, the viscosity of the third slurry is not less than 1 Pa·s, preferably 1-2 Pa·s. This preferred embodiment is beneficial to improving the mechanical strength of the catalyst.

[0078] The viscosity of the present invention is measured by a viscometer.

[0079] The solid content of the fourth slurry of the present invention is 40-50wt%, such as 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, and any value in the range formed by any two of these values. By adopting this preferred embodiment, the prepared catalyst takes into account both high mechanical strength and high molecular sieve ratio. When the solid content range of the fourth slurry is lower than the above range, the mechanical strength of the catalyst microspheres is poor. When the solid content range of the fourth slurry is higher than the above range, the catalyst slurry is easy to solidify quickly and has poor fluidity, which is not conducive to the subsequent spray drying.

[0080] The present invention has no particular limitation on the specific conditions of pulping (mentioned above and below) in the preparation method, and it can be carried out by conventional methods in the art, which is not limited here.

[0081] According to the present invention, preferably, the amounts of the clay, molecular sieve and binder precursor are such that in the prepared catalyst, based on the total mass of the catalyst, the mass content of the clay is 5-20%, preferably 5-15%; the mass content of the molecular sieve is 60-85%, preferably 60-70%; the mass content of the binder is 10-35%, preferably 18-30%; and the binder is the sum of the first binder, the second binder and the third binder.

[0082] According to the present invention, preferably, the dry weight ratio of the second binder precursor to the first binder precursor is 1-4, preferably 1.7-4.

[0083] According to the present invention, preferably, the dry basis mass ratio of the second binder precursor to the third binder precursor is 0.3-1, preferably 0.3-0.8.

[0084] According to the present invention, preferably, the first binder precursor is selected from at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina.

[0085] According to the present invention, preferably, the second binder precursor is aluminum sol.

[0086] According to the present invention, preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3.

[0087] The present invention has no particular limitation on the source of the aluminum sol, which can be obtained from commercial sources or prepared in-house according to conventional methods.

[0088] According to the present invention, preferably, the third binder precursor is phosphate aluminum gel.

[0089] According to the present invention, preferably, the phosphate aluminum gel has a network structure.

[0090] According to the present invention, preferably, Al in the phosphate aluminum gel 2 O 3 With P 2 O 5 The mass ratio is 0.25-0.35.

[0091] According to the present invention, preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3, for example 1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, and any value in the range formed by any two of these values.

[0092] The present invention has no particular limitation on the preparation method of the above-mentioned phosphate aluminum gel, as long as the phosphate aluminum gel with the above-mentioned composition and characteristics can be prepared. In order to further improve the catalytic performance of the catalyst, the present invention also provides a preparation method of the above-mentioned phosphate aluminum gel.

[0093] According to the present invention, preferably, the method for preparing the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel.

[0094] According to the present invention, preferably, the reaction conditions include: temperature of 75-85° C., and time of 1-2 h.

[0095] In the preparation method of the phosphate aluminum gel described in the present invention, by controlling the temperature of adding phosphoric acid, preferably further controlling the reaction conditions, the composition and characteristics of the prepared phosphate aluminum gel meet the above requirements, which is conducive to making the prepared catalyst have excellent catalytic performance.

[0096] The present invention has no particular limitation on the amount of the acid-soluble aluminum precursor and the phosphoric acid solution, so that in the obtained phosphate aluminum gel, Al 2 O 3 With P 2 O 5 The mass ratio is 0.25-0.35.

[0097] The present invention has no particular limitation on the amount of water used, as long as the pH of the phosphate aluminum gel is within the above range.

[0098] The present invention has a wide range of choices for the acid-soluble aluminum precursor, which can be a conventional choice in the art. Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide, preferably pseudo-boehmite.

[0099] The present invention has no particular limitation on the order of adding the molecular sieve, the second suspension containing clay and the first binder precursor in step (1), and they can be added separately or together. The embodiment of the present invention adopts the method of adding together as an example.

[0100] According to the present invention, preferably, the average particle size of the molecular sieve in step (1) is 0.5-2 microns, preferably 0.5-1 microns. This preferred embodiment is beneficial to improving the catalytic performance of the catalyst and the mechanical strength of the catalyst.

[0101] The average particle size of the molecular sieve in step (1) of the present invention is measured by a laser particle size analyzer method, see ASTM D4464-00 (2005) for details.

[0102] The present invention has no particular limitation on how to obtain the above-mentioned average particle size of the molecular sieve, and conventional technical means in the art may be used. The present invention uses a ball milling method for example.

[0103] Preferably, the molecular sieve is provided in the form of a first suspension.

[0104] The present invention has a wide range of choices for the type of the first liquid medium in the first suspension, which can be a conventional choice in the art. Preferably, the first liquid medium is water and / or an organic solvent, preferably water.

[0105] The present invention has no particular limitation on the amount of the first liquid medium in the first suspension, as long as the solid content in the first suspension is within 30-40 wt %.

[0106] According to the present invention, preferably, the second suspension is obtained by slurrying clay, the second liquid medium and optionally the remaining part of the second binder precursor. With this preferred embodiment, the clay has good fluidity while ensuring that the solid content of the second suspension is maintained at a high level.

[0107] According to the present invention, preferably, the dry basis mass of the remaining second binder precursor is 5-15% of the dry basis mass of the clay.

[0108] The present invention has a wide range of choices for the type of the second liquid medium in the second suspension, and can be a conventional choice in the art.

[0109] According to a preferred embodiment of the present invention, the second liquid medium is of the same type as the first liquid medium.

[0110] The present invention has no particular limitation on the amount of the second liquid medium in the second suspension, as long as the solid content in the second suspension is within the range of 28-38 wt %.

[0111] Preferably, the first binder precursor is provided in the form of a third suspension.

[0112] Preferably, the preparation method of the third suspension comprises: firstly slurrying the first binder precursor and the third liquid medium, and then mixing them with an acid.

[0113] According to the present invention, preferably, the acid is an inorganic acid, preferably hydrochloric acid and / or nitric acid. The above substances are conventionally selected in the art and can be obtained commercially.

[0114] Preferably, the weight ratio of the acid to the first binder precursor on a dry basis is 0.1-1:1.

[0115] The present invention has a wide range of choices for the type of the third liquid medium in the third suspension, which can be a conventional choice in the art.

[0116] According to a preferred embodiment of the present invention, the third liquid medium is of the same type as the first liquid medium.

[0117] The present invention has no particular limitation on the amount of the third liquid medium in the third suspension, as long as the solid content in the third suspension is within the range of 10-25 wt %.

[0118] The present invention has a wide range of molecular sieve types, which can be conventionally selected in the art. Preferably, the molecular sieve is at least one of ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve.

[0119] The present invention has a wide range of clay types, which can be selected from conventional choices in the art. Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.

[0120] According to the present invention, preferably, the mass dosage of the water absorbing agent is 0.05-1.5% of the dry mass of the third slurry, preferably 0.1-1%.

[0121] The present invention has a wide range of selection for the type of the water absorbent. In order to further improve the mechanical strength and catalytic performance of the catalyst, preferably, the water absorbent is selected from at least one of sodium polyacrylate, cellulose and its derivatives and chitosan and its derivatives, preferably selected from at least one of sodium polyacrylate, sodium carboxymethyl cellulose and chitosan.

[0122] The present invention has no particular limitation on the molecular weight of the water absorbing agent. Preferably, the weight average molecular weight of the water absorbing agent is 50,000-250,000.

[0123] According to the present invention, preferably, the inlet air temperature of the spray drying in step (5) is 250-400° C., preferably 300-400° C.; the outlet air temperature is 100-250° C., preferably 150-200° C. With this preferred embodiment, the spray drying temperature is suitable, which is conducive to obtaining the catalyst microspheres of the strength described in the present invention.

[0124] The present invention has no particular limitation on the conditions for the calcination in step (5), and the calcination may be carried out according to conventional methods in the art. Preferably, the calcination conditions in step (5) include: a temperature of 400-800° C. and a time of 1-12 h. The calcination is generally carried out in an air atmosphere, which may include a flowing atmosphere or a static atmosphere.

[0125] In the present invention, the "first", "second" and "third" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.

[0126] The third aspect of the present invention provides an application of the catalytic cracking catalyst described in the first aspect or the catalytic cracking catalyst prepared by the method described in the second aspect in a catalytic cracking reaction, preferably in a catalytic cracking reaction of naphtha.

[0127] The present invention has no particular limitation on the conditions of the catalytic cracking reaction, and the reaction can be carried out according to conventional methods in the art.

[0128] In order to better illustrate the stability of the catalyst of the present invention in the application of catalytic cracking reaction, it was hydrothermally aged before use.

[0129] The hydrothermal aging temperature of the catalytic cracking catalyst in the prior art is generally not more than 800°C, and the time is also relatively short, generally not more than 17 hours. The aging conditions of the hydrothermal aging described in the present invention are more stringent, and are used to better reflect the actual application degree of the industry. Preferably, the hydrothermal aging conditions include: a temperature of 820-850°C and a time of 20-72 hours.

[0130] Preferably, the hydrothermal aging is carried out under the condition of 100% water vapor.

[0131] The present invention will be described in detail below through examples.

[0132] In the following examples, the aluminum sol is a commercial product of Sinopec Catalyst Company Qilu Branch, with a solid content of 21.5% by weight;

[0133] Pseudo-boehmite is a commercial product from Shandong Aluminum Plant, with a solid content of 66.9 wt %;

[0134] ZSM-5 molecular sieve is a commercial product of Tianjin Nanhua Catalyst Co., Ltd., with a dry basis content of 97.8% by weight;

[0135] ZSM-22 molecular sieve is a commercial product of Tianjin Nanhua Catalyst Co., Ltd., with a dry basis content of 98.5% by weight;

[0136] Kaolin was a commercial product from Suzhou Kaolin Company, with a dry basis content of 84.6 wt %;

[0137] Sodium carboxymethyl cellulose is a commercial product of Shanghai Aladdin Biochemical Technology Co., Ltd., with a weight average molecular weight of 250,000;

[0138] Chitosan is a commercial product of Shanghai Aladdin Biochemical Technology Co., Ltd., with a weight average molecular weight of 150,000;

[0139] Sodium polyacrylate is a commercial product of Shanghai Aladdin Biochemical Technology Co., Ltd., and has a weight average molecular weight of 50,000.

[0140] Preparation Examples 1-3 are used to illustrate the preparation of the phosphoaluminum gel described in the present invention.

[0141] Preparation Example 1

[0142] Weigh 0.55 kg of pseudo-boehmite and 1.45 kg of deionized water and slurry them evenly, then heat to 50°C, add 2.00 kg of phosphoric acid (concentration 85 wt%), heat to 80°C and react for 90 minutes to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure, Al 2 O 3 With P 2 O 5 The mass ratio is 0.3 and the pH is 2.

[0143] Preparation Example 2

[0144] Weigh 0.51 kg of pseudo-boehmite and 1.41 kg of deionized water and slurry them evenly, then heat to 45°C, add 2.00 kg of phosphoric acid (concentration 85 wt%), heat to 80°C and react for 60 min to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure, Al 2 O 3 With P 2 O 5 The mass ratio is 0.28 and the pH is 2.2.

[0145] Preparation Example 3

[0146] Weigh 0.64 kg of pseudo-boehmite and 1.45 kg of deionized water and slurry them evenly, then heat to 55°C, then add 2.00 kg of phosphoric acid (concentration 85 wt%), heat to 75°C, and react for 60 minutes to prepare phosphoaluminum gel. The phosphoaluminum gel has a network structure, Al 2 O 3 With P 2 O 5 The mass ratio is 0.35 and the pH is 2.5.

[0147] Example 1

[0148] Weigh 6.65 kg of ZSM-5 molecular sieve with an average particle size of 0.6 μm obtained by ball milling and slurry it with deionized water to prepare a ZSM-5 molecular sieve suspension with a solid content of 33 wt%. Weigh 1.18 kg of kaolin, 0.47 kg of aluminum sol and deionized water respectively and slurry it to prepare a kaolin suspension with a solid content of 38 wt%. Weigh 0.45 kg of pseudo-boehmite and slurry it with deionized water, then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.13) to prepare a pseudo-boehmite suspension with a solid content of 17 wt%. Slurry the above-mentioned kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 2.33 kg of aluminum sol to the first slurry and slurry it for 5 minutes to obtain a second slurry. 4 kg of the phosphate aluminum gel prepared in the above-mentioned Preparation Example 1 was added to the second slurry and beaten for 5 minutes to obtain a third slurry. Sodium carboxymethyl cellulose was added to the third slurry and beaten for 10 minutes to obtain a fourth slurry. The fourth slurry was spray dried and then calcined at 550°C for 2 hours to obtain a catalyst. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.

[0149] Example 2

[0150] Weigh 6.13 kg of ZSM-5 molecular sieve with an average particle size of 0.92 μm obtained by ball milling and slurry it evenly with deionized water to prepare a ZSM-5 molecular sieve suspension with a solid content of 36 wt%. Weigh 1.77 kg of kaolin, 0.70 kg of aluminum sol and deionized water respectively and slurry it evenly to prepare a kaolin suspension with a solid content of 38 wt%. Weigh 0.48 kg of pseudo-boehmite and slurry it evenly with deionized water, and then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.12) to prepare a pseudo-boehmite suspension with a solid content of 21 wt%. Slurry the above-mentioned kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 2.09 kg of aluminum sol to the first slurry and slurry it for 5 minutes to obtain a second slurry. 3.92 kg of phosphoaluminum colloid obtained in the above-mentioned Preparation Example 2 was added to the second slurry and slurried for 5 minutes to obtain a third slurry. Chitosan was added to the third slurry and slurried for 10 minutes to obtain a fourth slurry. The fourth slurry was spray dried and then calcined at 550° C. for 2 hours to obtain a catalyst. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.

[0151] Example 3

[0152] Weigh 7.16 kg of ZSM-22 molecular sieve with an average particle size of 0.73 μm obtained by ball milling and slurry it with deionized water to prepare a ZSM-22 molecular sieve suspension with a solid content of 31 wt%. Weigh 0.83 kg of kaolin, 0.33 kg of aluminum sol and deionized water respectively and slurry it to prepare a kaolin suspension with a solid content of 32 wt%. Weigh 0.30 kg of pseudo-boehmite and slurry it with deionized water, then add hydrochloric acid (the weight ratio of the acid to the first binder precursor on a dry basis is 0.1) to prepare a pseudo-boehmite suspension with a solid content of 20 wt%. Slurry the above-mentioned kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 2.09 kg of aluminum sol to the first slurry and slurry it for 5 minutes to obtain a second slurry. 4.09 kg of phosphate aluminum gel prepared in the above-mentioned Preparation Example 3 was added to the second slurry and slurried for 5 minutes to obtain a third slurry. Sodium polyacrylate was added to the third slurry and slurried for 10 minutes to obtain a fourth slurry. The fourth slurry was spray dried and then calcined at 550°C for 2 hours to obtain a catalyst. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.

[0153] Comparative Example 1

[0154] The method of Example 1 was followed, except that no water absorbent was added, and the obtained third slurry was directly spray-dried and calcined to obtain a catalyst. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.

[0155] Comparative Example 2

[0156] Weigh 4.09 kg of ZSM-5 molecular sieve with an average particle size of 0.66 μm obtained by ball milling and slurry it with deionized water to prepare a ZSM-5 molecular sieve suspension with a solid content of 30 wt%. Weigh 2.96 kg of kaolin and slurry it with deionized water to prepare a kaolin suspension with a solid content of 35 wt%. Weigh 1.49 kg of pseudo-boehmite and slurry it with deionized water to prepare a kaolin suspension with a solid content of 35 wt%. Then add hydrochloric acid (the weight ratio of the acid to the pseudo-boehmite first binder precursor on a dry basis is 0.12) to prepare a pseudo-boehmite suspension with a solid content of 20 wt%. Slurry the above kaolin suspension, pseudo-boehmite suspension and molecular sieve suspension for 15 minutes to obtain a first slurry. Add 4 kg of phosphatic aluminum gel obtained in the above Preparation Example 1 to the first slurry to obtain a second slurry. The second slurry is spray dried and then calcined at 550° C. for 2 hours to obtain a catalyst. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.

[0157] Comparative Example 3

[0158] The catalyst was obtained by following the method of Example 1, except that 2.33 kg of phosphoaluminum colloid was added to the second slurry and 4 kg of aluminum sol was added to the third slurry. Some conditions in the catalyst preparation process are shown in Table 1. The catalyst composition and characteristic parameters are shown in Table 2.

[0159] Table 1

[0160]

[0161] Table 2

[0162]

[0163] Note: A represents the mass ratio of the second binder to the first binder

[0164] B represents: the mass ratio of the second binder to the third binder

[0165] Test Example 1

[0166] The catalysts prepared in the examples and comparative examples were subjected to hydrothermal aging treatment at 820°C, 100% steam, for 20 hours, and then subjected to naphtha cracking reaction evaluation. The detailed conditions for micro-reaction evaluation are: catalyst loading 9.0g, feedstock oil is Yanshan Changding naphtha, the composition of which is shown in Table 3, catalyst-to-oil ratio (mass ratio of catalyst to naphtha) is 10, and reaction temperature is 600°C. The evaluation data of the reaction for 90 seconds are shown in Table 4.

[0167] Table 3

[0168]

[0169]

[0170] Note: C Num Refers to the number of carbons.

[0171] Table 4

[0172]

[0173] It can be seen from the results in Table 4 that the application of the catalyst of the present invention in the catalytic cracking reaction of naphtha has a higher reactant conversion rate and a higher ethylene and propylene yield. At the same time, it can be shown from Table 4 that the catalyst of the present invention has good hydrothermal stability.

[0174] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalytic cracking catalyst, characterized in that: The catalyst comprises molecular sieve, binder and clay; Based on the total mass of the catalyst, the mass content of the molecular sieve is 60-85%, the mass content of the clay is 5-20%, and the mass content of the binder is 10-35%; The straight tube wear index of the obtained catalyst is no more than 3% / h, and the thermal wear index is no more than 7% / (5h).

2. The catalyst according to claim 1, wherein The adhesive comprises a first adhesive, a second adhesive and a third adhesive; Preferably, the first binder is obtained by calcining at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a Bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina; Preferably, the second binder is obtained by calcining aluminum sol; Preferably, the third binder is obtained by calcining phosphate aluminum glue.

3. The catalyst according to claim 2, wherein The aluminum sol has an aluminum-chlorine ratio of no more than 1.4, preferably 1.2-1.3; Preferably, the phosphate aluminum gel has a mesh structure; Preferably, the mass ratio of Al2O3 to P2O5 in the phosphate aluminum gel is 0.25-0.35; Preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3; Preferably, the preparation method of the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel; Preferably, the reaction conditions include: temperature of 75-85°C, time of 1-2h; Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide.

4. The catalyst according to claim 2, wherein Based on the total mass of the catalyst, the mass content of the molecular sieve is 60-70%, the mass content of the clay is 5-15%, and the mass content of the binder is 18-30%; Preferably, the mass ratio of the second binder to the first binder is 1-4, preferably 1.7-4; Preferably, the mass ratio of the second binder to the third binder is 0.3-1, preferably 0.3-0.8; Preferably, the molecular sieve is at least one selected from ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve; Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.

5. The catalyst according to any one of claims 1 to 4, wherein The straight tube wear index of the obtained catalyst is 0.5-3% / h, and the thermal wear index is 2.5-7% / (5h).

6. A method for preparing a catalytic cracking catalyst, the method comprising: (1) slurrying the molecular sieve, the second suspension containing clay, and the first binder precursor to obtain a first slurry; (2) slurrying the first slurry and at least a portion of the second binder precursor to obtain a second slurry having a viscosity of no more than 0.1 Pa·s; (3) beating the second slurry and the third binder precursor to obtain a third slurry having a viscosity of not less than 1 Pa·s; (4) beating the third slurry with a water absorbent to obtain a fourth slurry having a solid content of 40-50 wt %; (5) The fourth slurry is spray-dried and then calcined.

7. The method according to claim 6, wherein: The clay, molecular sieve and binder precursor are used in such amounts that, based on the total mass of the catalyst, the mass content of the clay in the prepared catalyst is 5-20%, preferably 5-15%; the mass content of the molecular sieve is 60-85%, preferably 60-70%; the mass content of the binder is 10-35%, preferably 18-30%; the binder is the sum of the first binder, the second binder and the third binder; Preferably, the dry basis mass ratio of the second binder precursor to the first binder precursor is 1-4, preferably 1.7-4; Preferably, the dry basis mass ratio of the second binder precursor to the third binder precursor is 0.3-1, preferably 0.3-0.

8.

8. The method according to claim 6, wherein: The first binder precursor is selected from at least one of pseudo-boehmite, hydrated alumina with a diaspore structure, hydrated alumina with a gibbsite structure, hydrated alumina with a Bayerite structure, γ-alumina, η-alumina, θ-alumina and x-alumina; Preferably, the second binder precursor is aluminum sol; Preferably, the aluminum sol has an aluminum-chlorine ratio of no higher than 1.4, preferably 1.2-1.3; Preferably, the third binder precursor is phosphate aluminum glue; Preferably, the phosphate aluminum gel has a mesh structure; Preferably, the mass ratio of Al2O3 to P2O5 in the phosphate aluminum gel is 0.25-0.35; Preferably, the pH of the phosphate aluminum gel is 1-3, preferably 2-3; Preferably, the preparation method of the phosphate aluminum gel comprises: mixing an acid-soluble aluminum precursor with water for slurrying, and then adding a phosphoric acid solution at 45-55° C. to react to obtain the phosphate aluminum gel; Preferably, the reaction conditions include: temperature of 75-85°C, time of 1-2h; Preferably, the acid-soluble aluminum precursor is selected from at least one of pseudo-boehmite, aluminum oxide, aluminum hydroxide, aluminum isopropoxide and aluminum isobutoxide.

9. The method according to any one of claims 6 to 8, wherein: The average particle size of the molecular sieve in step (1) is 0.5-2 microns, preferably 0.5-1 micron; Preferably, the second suspension is obtained by slurrying clay, a second liquid medium and optionally a remaining portion of a second binder precursor; Preferably, the dry basis mass of the remaining second binder precursor is 5-15% of the dry basis mass of the clay; Preferably, the molecular sieve is at least one selected from ZSM-5 molecular sieve, IM-5 molecular sieve and ZSM-22 molecular sieve; Preferably, the clay is selected from at least one of kaolin, halloysite, reuterite and montmorillonite.

10. The method according to any one of claims 6 to 9, wherein: The mass dosage of the water absorbent is 0.05-1.5% of the dry mass of the third slurry, preferably 0.1-1%; Preferably, the water absorbent is selected from at least one of sodium polyacrylate, sodium carboxymethyl cellulose and chitosan; Preferably, the air inlet temperature of the spray drying in step (5) is 250-400°C, preferably 300-400°C; the air outlet temperature is 100-250°C, preferably 150-200°C.

11. Use of the catalytic cracking catalyst according to any one of claims 1 to 5 or the catalytic cracking catalyst obtained by the method according to any one of claims 6 to 10 in a catalytic cracking reaction, preferably in a catalytic cracking reaction of naphtha.

Citation Information

Patent Citations

  • Multi-zeolite catalyzer for preparation of low-carbon olefines

    CN1048428C

  • Process for preparing cracking catalyst of petroleum hydrocarbons

    CN1119390C

  • Highly productive lower carbon olefin catalyst

    CN1272406C

  • Catalytic cracking catalyst capable of increasing yield of gasoline and preparation method thereof

    CN109304209A

  • Catalytic cracking catalyst as well as preparation method and application thereof

    CN112138710A